Mosquito saliva alone has profound effects on the human immune system. - Megan B Vogt; Anismrita Lahon; Ravi P Arya; Alexander R Kneubehl; Jennifer L Spencer Clinton; Silke Paust; Rebecca Rico-Hesse (Public Library of Science (PLoS), 2018)
Mosquito saliva is a very complex concoction of >100 proteins, many of which have unknown functions. The effects of mosquito saliva proteins injected into our skin during blood feeding have been studied mainly in mouse models of injection or biting, with many of these systems producing results that may not be relevant to human disease. Here, we describe the numerous effects that mosquito bites have on human immune cells in mice engrafted with human hematopoietic stem cells. We used flow cytometry and multiplex cytokine bead array assays, with detailed statistical analyses, to detect small but significant variations in immune cell functions after 4 mosquitoes fed on humanized mice footpads. After preliminary analyses, at different early times after biting, we focused on assessing innate immune and subsequent cellular responses at 6 hours, 24 hours and 7 days after mosquito bites. We detected both Th1 and Th2 human immune responses, and delayed effects on cytokine levels in the blood, and immune cell compositions in the skin and bone marrow, up to 7 days post-bites. These are the first measurements of this kind, with human immune responses in whole animals, bitten by living mosquitoes, versus previous studies using incomplete mouse models and salivary gland extracts or needle injected saliva. The results have major implications for the study of hematophagous insect saliva, its effects on the human immune system, with or without pathogen transmission, and the possibility of determining which of these proteins to target for vaccination, in attempts to block transmission of numerous tropical diseases.